De novo approach for the synthesis of water-soluble interlocked and non-interlocked organic cages. Issue 33 (24th March 2021) - Chakraborty, Debsena; Modak, Ritwik; Howlader, Prodip; Mukherjee, Partha Sarathi
Abstract : A water-soluble interlocked organic cage has been prepared without using dynamic covalent chemistry, and by controlling the transition state by using positional isomers, its analogous non-interlocked form has also been realised. Abstract : Research on self-assembled metallosupramolecular architectures has bloomed in recent times. Analogous metal–free organic architectures with water solubility are highly challenging. We report here a unique class of triazine based immidazolium water-soluble metal–free interlocked organic cage (1 ), which was synthesized in a one-pot reaction without using dynamic covalent chemistry and without any chromatographic separation. An analogous non-interlocked cage (2 ) was also successfully achieved by steric control using different positional isomers of the building blocks.